Landmarks of American language and linguistics (United States Department of State, 2000)
The book includes: The pronunciation component in teaching english to speakers of other languages; Grammar pedagogy in second and foreign language teaching; Questions, consequences, and conclusions; Talking to foreigners versus talking to children.